Screening Strategy of Active Pulmonary Tuberculosis in Sheltered Homeless People in Marseille, 2019 - Tran Duc Anh Ly; Floriane Holi-Jamovski; Van Thuan Hoang; Ndiaw Goumballa; Meriem Louni; Thi Loi Dao; Michel Drancourt; Philippe Gautret (Springer, 2020)
We aimed to assess the reliability of a screening questionnaire for Active Pulmonary Tuberculosis (APTB) in a population of sheltered homeless persons (HP). Participants from two homeless shelters completed a questionnaire specially designed to identify patients at high-risk of APTB (available at www.tb-screen.ch), underwent a Chest X-ray (CXR), and provided sputum samples. Computed Tomography (CT) scanning was subsequently performed on those which had images consistent with APTB. Microscopical examination, real-time polymerase chain reaction (qPCR) and culture testing were applied for Mycobacterium tuberculosis complex detection. Additionally, we retrospectively selected 16 HP hospitalised in our hospital between 2017 and 2019 with biologically confirmed tuberculosis and typical CXR images, and retrospectively documented a screening questionnaire by reviewing their medical files. Overall, the population (n = 383 HP) was predominantly migrants (87%). Forty-seven individuals (11.7%) had positive screening questionnaire scores and four (2.4%) displayed abnormal CXR features consistent with APTB. Three of them three underwent CT scanning that ruled out APTB and one was lost to follow-up. None tested positive through microbiological investigation. Fifteen (of 16, 93.8%) hospitalised patients with biologically confirmed APTB had a positive screening questionnaire score. The sensitivity and specificity of questionnaire for confirmed APTB were 93.8% and 87.7%, respectively. Screening questionnaires can be used as a first assessment tool in people arriving at homeless shelters and to refer those screening positive for a CXR.